2019
DOI: 10.1111/jfbc.12962
|View full text |Cite
|
Sign up to set email alerts
|

The plant flavonoid, fisetin alleviates cigarette smoke‐induced oxidative stress, and inflammation in Wistar rat lungs

Abstract: In the present study, we tested the antioxidant and anti‐inflammatory potential of the plant flavonoid, fisetin against cigarette smoke‐induced oxidative stress, and inflammation in rat lungs. Male Wistar rats were chronically exposed to cigarette smoke (CS) with or without administration of fisetin. Fisetin administration to CS‐exposed rats resulted in a significant reduction in neutrophils and macrophages in bronchoalveolar lavage fluid as well as malondialdehyde, 3‐nitrotyrosine, 8‐isoprostane, tumor necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Fisetin, a plant flavonoid present in Gleditsiae spina , has been shown to be effective in lowering inflammation and oxidative stress associated with different disease conditions. Fisetin (25 or 50 mg) demonstrated a significant decrease in inflammatory mediators such as TNF- α , granulocyte-macrophage colony-stimulating factor (GM-CSF), and interleukin (IL)-1 β , IL-4, and IL-10 [ 44 ]. The anti-inflammatory mechanism of fisetin was related to suppressing the TNF- α -activated NF- κ B cascade via targeting protein kinase C [ 33 ].…”
Section: Roles Of Flavonoids On Chronic Obstructive Pulmonary Disementioning
confidence: 99%
“…Fisetin, a plant flavonoid present in Gleditsiae spina , has been shown to be effective in lowering inflammation and oxidative stress associated with different disease conditions. Fisetin (25 or 50 mg) demonstrated a significant decrease in inflammatory mediators such as TNF- α , granulocyte-macrophage colony-stimulating factor (GM-CSF), and interleukin (IL)-1 β , IL-4, and IL-10 [ 44 ]. The anti-inflammatory mechanism of fisetin was related to suppressing the TNF- α -activated NF- κ B cascade via targeting protein kinase C [ 33 ].…”
Section: Roles Of Flavonoids On Chronic Obstructive Pulmonary Disementioning
confidence: 99%
“…Fisetin (FIS), a natural non-toxic flavonoid, is present in various plants, fruits and vegetables. Previous researches have demonstrated that FIS has anti-inflammatory (Huang et al, 2018), anti-fibrosis, anti-oxidant (Hussain et al, 2019) and anti-aging properties (Yousefzadeh et al, 2018). FIS supplementation can prevent or alleviate hepatic and myocardial fibrosis by inhibiting the expression of fibrosisrelated genes and inactivating TGF-β1/Smad3 signaling (Liu et al, 2019;Choi et al, 2020;Hu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Below we will discuss the protective mechanisms of HO-1/CO in respiratory inflammatory diseases. We particularly focus on herbal medicines with the potential to induce HO-1 expression, including salvianolic acid A, 87 asiatic acid, 41 celastrol, 88 fisetin, 89 galangin, 90,91 kaempferol, [92][93][94][95] luteolin, 96 madecassoside, 97,98 oleanolic acid, 99,100 saikosaponin A, 101 2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oic acid (CDDO), 102 and pristimerin. 49,103 In the following sections, the detailed pharmacological mechanisms of these herb ingredients will be further discussed.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…255 Conversely, Hussain et al revealed that in lungs exposed to CS, fisetin attenuated inflammation and oxidative stress to protect the lung from CS-mediated injury via the Nrf2dependent expression of antioxidative genes (HO-1, glutathione peroxidase-2, reduced GSH, SOD) to reduce the infiltration of inflammatory cells and cytokine expression. 89 Galangin Galangin (3,5,7-trihydroxyflavone) is found in Alpinia officinarum and honey in high concentrations and is submit your manuscript | www.dovepress.com…”
Section: Fisetinmentioning
confidence: 99%